Relationship between vitamin K dependent coagulation factors and anticoagulants (protein C and protein S) in neonatal vitamin K deficiency. Issue 3 (March 1993) - Matsuzaka, T; Tanaka, H; Fukuda, M; Aoki, M; Tsuji, Y; Kondoh, H
Abstract : To determine the relationship between vitamin K dependent coagulation factors and natural anticoagulants, namely protein C and protein S, in various degrees of vitamin K deficiency, plasma values for clotting activity, protein induced by vitamin K absence (PIVKA-II), protein C antigen, gamma-carboxy protein C antigen, and protein S antigen including total and free fractions and activity of protein C were measured in 66 full term and healthy breast fed neonates who did not receive vitamin K supplement at birth. The 66 neonates were divided into a control group (17 cases) and a low group (49 cases) according to their values for clotting activity–that is, > or = 20% or < 20% during the first six days of life–and vitamin K was immediately given when the neonates showed values < 20%. In the low group clotting activity gamma-carboxy protein C, free protein S, and protein C activity was significantly decreased to a minimum on day 2 or 3, and increased in parallel after vitamin K administration. Furthermore, they were positively correlated with one another and inversely cor-correlated with the PIVKA-II concentrations. These findings suggest that simultaneous gamma-carboxylation of coagulation factors and proteins C and S acts to maintain both coagulation and anticoagulation activities in parallel at various concentrations of vitamin K. The breast milk intake in the group with low values of clotting activity was significantly lower than that in the control group during the first three days of life.(ABSTRACT TRUNCATED AT 250 WORDS)